Metal Availability and Transfer along Food Chains in Siena, a Small Medieval Town in Italy - Emilia Rota; Nicola Bianchi; Roberto Bargagli (Journal of Chemistry)
Heavy metals originating from vehicular emissions and other anthropogenic sources pose one of the main environmental health risks in urban areas. The assessment of metal bioaccumulation in selected species of synanthropic organisms allows evaluating their bioavailability and the transfer along food chains in urban ecosystems. An overall view of the results achieved in Siena on urban ecosystems shows that the mean Cd, Cu, Pb, and Zn concentrations in biological crusts covering urban walls (0.66, 34, 65, and 184 μg·g−1 d.w.) are higher than the respective concentrations in tree leaf litter (0.19, 9.5, 9.2, and 38 μg·g−1 d.w.) and topsoil (0.40, 44, 34.2, and 102 μg·g−1 d.w.). Furthermore, the epilithic moss Tortula muralis accumulated much higher levels of Cd, Cu, Pb, and Zn (0.34, 65, 17.6, and 106 μg·g−1 d.w.) than epiphytic lichens (0.22, 11.6, 2.1, and 47.3 μg·g−1 d.w.) or the holm oak live foliage (0.15, 14, 1.51, and 26.5 μg·g−1 d.w.), respectively. However, analyses of the soft tissues of Papillifera papillaris, a snail dwelling on stone walls, show that metals deposited on urban walls are scarcely bioavailable. Papillifera accumulates (and transfers to the next trophic level) amounts of Cd, Cu, Pb, and Zn (1.7, 171, 1.1, and 71 μg·g−1 d.w., respectively) that are comparable or inferior to those found in a ground-dwelling snail (3.3, 88, 2.0, and 880 μg·g−1 d.w.) and two earthworm species (2.0–4.4, 18–23, 1.4–2.2, and 356–594 μg·g−1 d.w.) from the same urban green area.